Soil properties influence the toxicity and availability of Zn from ZnO nanoparticles to earthworms. (15th February 2023) - Lahive, E.; Matzke, M.; Svendsen, C.; Spurgeon, D.J.; Pouran, H.; Zhang, H.; Lawlor, A.; Glória Pereira, M.; Lofts, S.
Abstract: To develop models that support site-specific risk assessment for nanoparticles (NPs), a better understanding of how NP transformation processes, bioavailability and toxicity are influenced by soil properties is needed. In this study, the influence of differing soil properties on the bioavailability and toxicity of zinc oxide (ZnO) NPs and ionic Zn to the earthworm Eisenia fetida was investigated. Earthworms were exposed to ZnO_NPs and ionic Zn, between 100 and 4400 mg Zn/kg, in four different natural soils (organic matter content: 1.8–16.7%, soil pH: 5.4–8.3, representing sandy loam to calcareous soils). Survival and reproduction were assessed after 28 and 56 days, respectively. Zn concentrations in soil pore waters were measured while labile concentrations of Zn were measured using an in-situ dynamic speciation technique (diffusive gradient in thin films, DGT). Earthworm Zn tissue concentrations were also measured. Soil properties influenced earthworm reproduction between soil controls, with highest reproductive output in soils with pH values of 6–7. Toxicity was also influenced by soil properties, with EC50 s based on total Zn in soil ranging from 694 to >2200 mg Zn/kg for ZnO_NP and 277–734 mg Zn/kg for ionic Zn. Soil pore water and DGT measurements showed good agreement in the relative amount of Zn extracted across the four soils. Earthworms exposed to ZnO_NPs survived higher Zn concentrations in the soils and had higher tissue concentrations compared with ionic Zn exposures, particularly in the high organic content calcareous soil. These higher tissue concentrations in ZnO_NP exposed earthworm could have consequences for the persistence and trophic mobility of Zn in terrestrial systems and need to be further investigated to elucidate if there any longer-term risks associated with sustained input of ZnO_NP to soil. Graphical abstract: Image 1 Highlights: ZnO NP toxicity was lower compared to ionic Zn based on total Zn in soil. Zn in soil pore water in the NP-spiked soil was largely in the soluble form. DGT ultrafiltration indicated NPs were present in the labile fraction. Higher body burdens of Zn were found in NP-exposed earthworms. High pH and organic matter resulted in lower toxicity for both Zn forms.